Methodology of evaluation by formation of groups in a fi rst computer programming course using Collaborative Learning (2018)
This article presents the results of a specific methodology used with some programming courses where we conform groups of students with diff erent characteristics looking to improve the individual learning level in the learning process of computer programming in a Systems Engineer program. The target of this research was to explore an easy way to learn based on cooperation and collaboration between students. We realized tests in the programming courses by dividing the group in two subgroups based on some determined parameters. We conclude that the results bring a special light to consider as important inside the learning process of engineers so the experience could be very useful in other engineering programs and other areas.